Chemical Composition of Essential Oils and Mineral Contents of Zygophyllum gaetulum (Emb. and Maire). Issue 6 (2nd November 2017) - El Abdouni Khayari, M.; Benharref, A.; Abbad, A.; Bekkouche, K.; Larhsini, M.; Alaoui Jamali, C.; Markouk, M.; Taourirte, M.
Abstract: Essential oils were obtained by hydrodistillation of Zygophyllum gaetulum collected from Taguounite (south of Morocco). The chemical profiles of essential oils were evaluated by means of GC-MS method and in total, 33 compounds were identified from leaves, fruits and stem roots. Caryophyllene E was the major compound for leaves (19.18%), whereas Decanone and Bornylacetate were the major constituents for fruits and stem roots respectively with 31.5% and 33.84%. For mineral composition of leaves, According to results, calcium and sodium values were very high in leaves samples (2.8 and 1.73% of dried samples respectively). The levels of crud ash were of 20%. This result contributed to the nutritional properties of these plant species and may be useful for the evaluation of dietary information. Phytochemical screening have shown the presence of tannins, saponins, alkaloids, flavonoids and terpens.